Cytotoxic T-Cell Markers and Cytokines in Human Papillomavirus 16 - Sakineh Abbasi; Shahrzad Sharifpour Vajari (Tehran University of Medical Sciences, 2022)
Background and Aim: Cervical cancer is the fourth main cause of mortality among women, and annually about half a million new cases are detected in developed countries. Based on oncological studies, human papillomavirus (HPV) is classified into two categories: high-risk type and low-risk type, and most cases are related to the high-risk type of human papillomavirus. HPV 16 and 18 are among the more dangerous ones in this type of cancer. Human papillomavirus is a small group of uncoated viruses with double-stranded DNA that belong to the papillomaviridae family. Materials and Methods: In this review study, more than 200 articles related to human papillomavirus and immune system function against this virus were reviewed from 2015 to 2020 and among them, 34 articles related to markers and cytokines in cervical cancer were chosen from Google Scholar, Scopus, and PubMed. Results: One of In-vitro methods in markers detection , is using vectors to infect dendritic cells to present antigen, increase the expression of markers and mature T cell, which leads to the identification of a variety of markers and cytoklines such as PD, PDL, CD, MHC, FASL, IFN, IL, TLR associated with cervical cancer. Conclusion: Cervical cancer prevention can reduce the economic as well as the social burden of having the disease in the community.  Important cytokines expressed when exposed to HPV include IL-6 and IL-8. Several agonist epitopes with enhanced binding power to the human leukocyte antigen (HLA-A2) A2 class I antigen have been described to enhance cytotoxic T lymphocyte responses and to be used in the development of effective HPV vaccines; this is because it has already been shown that different epitopes of 16 HPVs, such as E6 and E7, are able to elicit human cytotoxic T lymphocyte (CTL) responses by binding to HLA-A2.